Cangrelor - rising from the ashes: a phoenix story - George, Melvin; Jena, Amrita; Karthikeyan, Balakrishnan (International Journal of Basic & Clinical Pharmacology, 2016)
Cangrelor is a novel intravenous antiplatelet agent that has been approved for usage in the setting of percutaneous coronary revascularization in patients with acute coronary syndrome. The drug was evaluated in three major trials namely Champion-Platform, Champion-PCI and Champion Phoenix with a total of 25,107 patients. Although there was a reduction in the incidence of ischemia driven revascularization, Q wave MI and stent thromboses in the first 48 hours among cangrelor users as compared to clopidogrel, there was no difference in the incidence of all-cause mortality or myocardial infarction. In terms of safety, cangrelor does not appear to have a higher bleeding risk. A distinct appeal with cangrelor is its unique pharmacokinetic property of having a rapid onset and offset of action. The drug would also have a niche role among patients with challenges to oral drug administration as in mechanically ventilated patients and those with severe vomiting. Although the drug managed to rise against odds in getting regulatory approval from the FDA, it remains to be seen if this could become a frontline agent among the current array of anti-platelet molecules.